Evaluating the echogenicity of ethyl cellulose-ethanol gel for tracking biodistribution during liver ablation - Jeffrey Yang; Xihan Ma; Andrew S. Mikhail; William F. Pritchard; Bradford J. Wood; Haichong K. Zhang; Jenna L. Mueller (Scientific Reports)
Abstract Hepatocellular carcinoma (HCC) is the third most common cause of cancer deaths worldwide. While surgery and liver transplantation are curative treatments for HCC, many tumors are unresectable due to co-morbidities or advanced stage. Ethanol ablation is an established alternative ablative therapy for HCC that is typically paired with ultrasound imaging to visualize tumors and enable precise ethanol delivery. However, ethanol has the propensity to leak from the injection site and is not inherently echogenic, making biodistribution difficult to monitor. To address these limitations, we added ethyl cellulose (EC) with ethanol to form a gel that improves ethanol retention and generates an echogenic depot in tissue. We performed studies in tissue phantoms and liver tissue to characterize the acoustic profile of the EC-ethanol depots. Studies in phantoms showed that the EC-ethanol depots were 1.5x more echogenic when EC-ethanol ratios increased from 6 to 12% (p < 0.001). EC-ethanol depots in excised liver tissue and in swine liver post-mortem were acoustically discernable and generated 4 cm2 depots, which are of clinically relevant size for HCC treatment. In summary, this study established the echogenic properties of EC-ethanol for spatiotemporal analysis of injectate distribution, demonstrating its translational potential for tracking biodistribution during liver ablation.